PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MEDIA PEMBELAJARAN VISUAL DENGAN AUDIOVISUAL KELAS X SMA PGRI 2 BANJARMASIN TAHUN AJARAN 2014/2015 - Hafiza Tiffanullah; Karunia Puji Hastuti; Deasy Arisanty (JPG (Jurnal Pendidikan Geografi), 2015)
The title of this research is “Perbedaan Hasil Belajar Siswa Menggunakan Media Pembelajaran Visual dan Audiovisual Kelas X SMA PGRI 2 Banjarmasin Tahun Ajaran 2014/2015”. The objective of this research is for examining the differences of students’ learning result between visual learning media with audiovisual learning media. The population in this research is an class X of SMA PGRI 2 Banjarmasin total students 164 people, the samples of this research are students of  X 1 as experimental class of visual learning media and students of X 2 as experimental class of audiovisual learning media, so there are 42 students as samples for this research. The method used in experiment with quantitative approach. Kind of data that used are primer data that found from the test of learning result and secunder data that found from observation and document study. This research is analysed by using Uji T technique, which is by using T test formula.The result of counting that can be found from the students taught by using visual learning media is > or 9,54 > 2,02 and from the students taught by using audiovisual learning media is > or 6,78 > 2,04. It means , there is a significance difference between pre-test result and post-test result. Because there is an increasing number from the mean of learning result , about 9,54 from visual learning media and 6,78 from audiovisual learning media. Because it bigger than, it means the differences of students’ learning result between visual learning media with audiovisual learning media is significance in table 0,05 and 0,01 so the hypothesis is can be accepted. Furthermore, geographic teachers can use visual learning median and audiovisual learning media in teaching and learning process as an effort for improving students’ learning result .Keywords: Differences Learning Result, Visual Learning Media, Audiovisual Learning Media.